ISLAMIC EDUCATION STRATEGIES IN FORMING STUDENT CHARACTER IN THE ERA OF INDUSTRIAL REOLUTION 4.0 - Aisyah, Ia Siti; Rahmatullah, Irfan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In the 4.0 era, the formation of student character is very important because technological progress is unstoppable and information can spread quickly. This research aims to find out how Islamic education strategies shape student character in the era of revolution 4.0. The research method used is descriptive with a qualitative-phenomenological approach. Data analysis uses Miles and Huberman's interactive model through four stages, which include: data collection, data reduction, data presentation, and drawing conclusions. The research results show that student character formation can be integrated with learning, example, a good environment, and habituation which is closely related to character education. To build the character of his students, a teacher must be an example for his students. Apart from that, Islamic religious education contributes to the formation of students' character through the following activities: (1) Intracurricular activities: In these activities, teachers incorporate character into the lessons of each subject, such as the Qur'an, Hadith, Fiqh, Islamic Cultural History, Arabic Language, and Moral Creeds. In this activity, the teacher is directly connected to the material on morality or character. (2) Extracurricular activities: Tilawati Several traits are built through these two types of activities: religious, honest, likes to read, responsible, independent, appreciates achievements, cares socially, and works hard. The students are ready to face the industrial era 4.0 with character. Islamic character will be formed by good cooperation between schools, parents and the community